The Impact of Digital Service Factors on Customer e-Loyalty through e-Satisfaction: A Study of ZUS Coffee - Louis Yong Yu Lee; Chen Yuen Yeoh; Hui Wen Yong; Jieen Yew; Ruo Han Yong; Aditya Kumar; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2026)
This study investigates how digital service factors influence customer e-satisfaction and e-loyalty in Malaysia’s increasingly digitalized coffee market, using the ZUS Coffee mobile application as the research context. Grounded in Expectation-Confirmation Theory and the Technology Acceptance Model, the study examines the roles of e-service quality, online price transparency, digital promotion exposure, and perceived e-convenience. Data were collected through a quantitative survey administered via Google Forms to Malaysian consumers who had prior experience using the ZUS Coffee mobile application, with non-users excluded through a screening question. A total of 180 valid responses were analyzed using IBM SPSS. The findings show that digital promotion exposure and perceived e-convenience are the primary drivers of customer e-satisfaction. In contrast, customer e-loyalty is shaped mainly by e-service quality, online price transparency, and digital promotion exposure. Notably, perceived e-convenience demonstrates a negative association with e-loyalty, while customer e-satisfaction does not directly lead to loyalty.